Laboratory Management System: General Requirements - Bharati, Pawan Kumar (Ed.); Kumar, Prasann (Ed.) (NEW DELHI: Discovery Publishing House, 2020)
The present book updates the subject content on Laboratory Management System; Effective Handling of Lab Instruments and Chemicals, Safety in Microbiology Laboratory, Cultivation of Great Work Habits; Quality Management Systems (QMS) - Requirements (ISO 9001:2015); Environmental Management Systems (EMS) ISO-14001 - Requirements with guidance, Occupational Health and Safety Management Systems (OHSAS-18001): Requirements; Integrated Management System (IMS) Manual; Good Laboratory Practice (GLP) Training Manual and Guidelines; OECD Principles of GLP.